PENGEMBANGAN MEDIA SCRAP POP-UP BOOK DALAM PEMBELAJARAN PPKN MATERI NILAI-NILAI PANCASILA UNTUK KELAS II SEKOLAH DASAR - Refila Azizah Gyat; Maharani Putri Kumalasani; Murtyas Galuh Danawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The teaching and learning process at SD Negeri 1 Arjosari Kalipare found problems in PPKn learning, students tend to be passive and quiet, besides lacking enthusiasm for learning. Lack of enthusiasm and interest in the material in PPKn, especially when the material on Pancasila and values ​​is quite a lot, thus reducing the understanding of the material given. During learning, students get material with the lecture method followed by questions and answers and discussions. These problems require learning media that can attract students' interest and activeness in learning. The purpose of this study is to develop scrap pop-up book media in PPKn learning on Pancasila values ​​material for grade II of Elementary School. This research method is a Research and Development (RnD) type of research using the ADDIE model with 5 stages: Analyze, Design, Development, Implementation, Evaluation. The research instruments used were observation sheets, interviews, material validation expert questionnaires, media validation expert questionnaires, teacher response questionnaires, and student response questionnaires. The data analysis techniques used were qualitative data analysis and quantitative data analysis. Based on the research, the results obtained are that to determine the validity of a media, a validation test needs to be carried out. The results of the material expert validation test showed a percentage of 97.5% with a very feasible category, and the results of the media validation test showed a percentage of 85.29% with a very feasible category. Meanwhile, for the student response questionnaire, the percentage was 97.5% and the teacher response questionnaire was 100%. There are also research findings in the use of media, it can be concluded that the scrap pop-up book learning media has provide an understanding of Pancasila values to students, and increasing student learning motivation.